CIVIL RESPONSIBILITY WITHIN THE TEACHING ROLE - Maira Alejandra Parrado Contreras; Yhon Fredy Franco (DIALÉCTICA, 2025)
Nowadays, educational systems are highly influenced by various factors and elements; all those transformations at the political, economic and social level have a direct impact on the conceptions that are held about the educational process. The teaching profession as a humanistic and purely social discipline is one of the main areas that undergoes great changes because of the conditions of the environment. Being a teacher today is not the same as being a teacher in the 20th century and even more so if this reality is perceived from the legal field. All the norms, laws and decrees in force demand a high level of commitment from practicing teachers since figures such as legality, due process, responsibility, among many other topics become a crucial part of the educational discourse. In this sense, this essay examines the complexity and implications of civil liability in the context of the teaching role in Colombia, exploring how social and legal demands influence the performance and obligations of educators. Through the analysis of cases and legal theories, the challenges and responsibilities faced by teachers in their daily practice are discussed, to conclude that it is necessary for the State to create a program whose objective is the legal protection of teachers in practice, to propose a reform to the regulations that govern legal sanctions for teachers, and to include legal training in the curriculum of undergraduate programs that train graduates in the country.